Generalization and improvement of Nyberg-Rueppel message recovery blind signatures - HUANG Zhen-jie1; WANG Yu-min2; CHEN Ke-fei1 (Tongxin xuebao)
A generalized Nyberg-Rueppel message recovery blind signature scheme was presented,from which the scheme proposed by Camenisch et al and two new schemes could be obtained.One of these two new schemes was an efficiently improved scheme without computing any inverse while Camenisch et al’s scheme needs.Moreover,using the padding technique and hash function,a provably secure message recovery blind signature scheme,against adaptive chosen-message attack in random oracle model and generic group model,was proposed.